Nanoscale Organization, Regulation, and Dynamic Reorganization of Cardiac Calcium Channels - Dixon, Rose E. (Frontiers in Physiology, 2022)
The architectural specializations and targeted delivery pathways of cardiomyocytes ensure that L-type Ca2+ channels (CaV1.2) are concentrated on the t-tubule sarcolemma within nanometers of their intracellular partners the type 2 ryanodine receptors (RyR2) which cluster on the junctional sarcoplasmic reticulum (jSR). The organization and distribution of these two groups of cardiac calcium channel clusters critically underlies the uniform contraction of the myocardium. Ca2+ signaling between these two sets of adjacent clusters produces Ca2+ sparks that in health, cannot escalate into Ca2+ waves because there is sufficient separation of adjacent clusters so that the release of Ca2+ from one RyR2 cluster or supercluster, cannot activate and sustain the release of Ca2+ from neighboring clusters. Instead, thousands of these Ca2+ release units (CRUs) generate near simultaneous Ca2+ sparks across every cardiomyocyte during the action potential when calcium induced calcium release from RyR2 is stimulated by depolarization induced Ca2+ influx through voltage dependent CaV1.2 channel clusters. These sparks summate to generate a global Ca2+ transient that activates the myofilaments and thus the electrical signal of the action potential is transduced into a functional output, myocardial contraction. To generate more, or less contractile force to match the hemodynamic and metabolic demands of the body, the heart responds to β-adrenergic signaling by altering activity of calcium channels to tune excitation-contraction coupling accordingly. Recent accumulating evidence suggests that this tuning process also involves altered expression, and dynamic reorganization of CaV1.2 and RyR2 channels on their respective membranes to control the amplitude of Ca2+ entry, SR Ca2+ release and myocardial function. In heart failure and aging, altered distribution and reorganization of these key Ca2+ signaling proteins occurs alongside architectural remodeling and is thought to contribute to impaired contractile function. In the present review we discuss these latest developments, their implications, and future questions to be addressed.